Communication Behaviour of Dairy Farmers: A Source for Milk Qulity Improvement - Vikram Singh , Jancy Gupta and M. S. Nain, (Indian Journal of Extension Education, 2014)
The present study was conducted in dairy cooperative system of Rajasthan state in organized sector i.e. RajasthanCooperative Dairy Federation (RCDF). A multistage proportionate random sampling procedure was applied to draw thesample for the study. Out of 21 unions four district milk unions were selected for the present study viz. Alwar, Bhilwara,Bikaner and Hanumangarh. A total of 120 farmers were selected on the basis of proportionate random sampling. Theresults of this study revealed that most of the dairy farmers used friends, progressive milk producers, veterinary officersand neighbours as information sources; group discussion, group meetings, newspaper and Dairy Cooperative Society(DCS) were important channels for information seeking about proper 'cattle shed' and 'milking procedure'. However, Milkroute supervisor, progressive milk producer, friends and neighbours were found as major information sources; whereas,DCS, educational tour and group discussion were important channels for information used by the dairy farmers forinformation seeking about 'cleaning of utensil' and 'post milking practices'.